Peningkatan Kualitas Belajar Melalui Kepemimpinan Pembelajaran Berbasis Deep Learning di SMPN 3 Margahayu - Mulyanto, Agus; Supriatna, Nana; Erawati, Erna Rostika; Heryati, Tuti; Mulyanah, Uyun (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
This community service activity aims to improve teachers' pedagogical competence through understanding and implementing the deep learning approach in the learning process at the Junior High School (SMP) level in Bandung Regency. The problems faced include the low readiness of teachers in implementing deep learning approaches due to limited conceptual understanding and practical skills, as well as the dominance of the lecture method in classroom management. This activity is based on the theory of constructive alignment from Biggs and Tang (2011) and the principles of mindful, meaningful, joyful learning launched by the Ministry of Education and Culture (2024), which emphasizes the importance of conceptual understanding, critical reflection, and active student involvement in learning. The implementation of activities uses a Service Learning approach combined with Participatory Action Research and Community-Based Research, which allows for educational interaction between the service team and teachers as participants. Activities are carried out in the form of face-to-face training and simulation of deep learning-based lesson planning. Evaluation was carried out through pretest and posttest which showed a significant increase from the average score of 68.2 to 88.7, with an average increase of 20.5 points. This result shows the effectiveness of the activity in improving teachers' theoretical and applicative understanding of the deep learning approach. The conclusion of this activity states that training and mentoring in the implementation of deep learning can strengthen the capacity of teachers as reflective, innovative and transformative learning leaders. This activity also makes a real contribution to improving the quality of learning in partner schools, and opens up opportunities for replication of similar activities in other educational units.ABSTRAKKegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kompetensi pedagogis guru melalui pemahaman dan implementasi pendekatan deep learning dalam proses pembelajaran di tingkat Sekolah Menengah Pertama (SMP) di Kabupaten Bandung. Permasalahan yang dihadapi meliputi rendahnya kesiapan guru dalam menerapkan pendekatan pembelajaran mendalam akibat keterbatasan pemahaman konseptual dan keterampilan praktis, serta dominasi metode ceramah dalam pengelolaan kelas. Kegiatan ini dilandasi oleh teori constructive alignment dari Biggs dan Tang (2011) serta prinsip mindful, meaningful, joyful learning yang dicanangkan Kemendikbud (2024), yang menekankan pentingnya pemahaman konseptual, refleksi kritis, dan keterlibatan aktif siswa dalam pembelajaran. Pelaksanaan kegiatan menggunakan pendekatan Service Learning yang dikombinasikan dengan Participatory Action Research dan Community-Based Research, yang memungkinkan terjadinya interaksi edukatif antara tim pengabdi dan guru sebagai peserta. Kegiatan dilakukan dalam bentuk pelatihan tatap muka dan simulasi penyusunan perencanaan pembelajaran berbasis deep learning. Evaluasi dilakukan melalui pretest dan posttest yang menunjukkan adanya peningkatan signifikan dari nilai rata-rata 68,2 menjadi 88,7, dengan kenaikan rata-rata 20,5 poin. Hasil ini menunjukkan efektivitas kegiatan dalam meningkatkan pemahaman guru secara teoretis maupun aplikatif terhadap pendekatan deep learning. Kesimpulan dari kegiatan ini menyatakan bahwa pelatihan dan pendampingan implementasi pembelajaran mendalam mampu memperkuat kapasitas guru sebagai pemimpin pembelajaran yang reflektif, inovatif, dan transformatif. Kegiatan ini juga memberikan kontribusi nyata terhadap peningkatan kualitas pembelajaran di sekolah mitra, serta membuka peluang replikasi kegiatan serupa di satuan pendidikan lainnya.